WISATA DRAMA SEBAGAI KEUNGGULAN DAYA TARIK WISATA: PERPADUAN ALAM DAN KREATIVITAS DI KOREA SELATAN - Dewa Ayu Diyah Sri Widari (Institut Pariwisata dan Bisnis Internasional, 2014)
Korea is a country that is famous for the production of its ginseng. In addition, the reliability of plastic surgery has also become one of the magnet that is able to attract tourists to visit the country. Another factor that makes Korea remains one of the tourist destinations that inspires the desire of tourists to visit the Korea is the booming of serial drama. Presentation of drama and romantic story combined with shooting location is built and developed into the tourist drama. Drama tour offered serves a fusion of nature and creativity as well as supported by the promotion of harmonization.This article is intended to find out the creativities from the drama tour in Korea tourist destinations. Specifically, this article can give you an idea of the expected utilization of the drama as one of tourist excellences and tourist attractions. In General, the article is expected to provide knowledge in the management of tourism. So that they are presented with a blend of nature and creativity as well as supported by the impressions of drama was able to give another view of tourist destinations.Â